Technology Use Analysis for Administrative Assistants by Using The Theory of Technology Acceptance Model - Ambarwati, Maria Francisca Lies (Jurnal Administrasi dan Kesekretarisan, 2021)
Working behaviour has changed because of the unprecedented condition of the Covid-19 pandemic. People manage to find new ways of doing their work from their house with the help of technology. Using the concept of Technology Acceptance Model (TAM), the purpose of this study was to reveal the perception of secretaries and administrative assistants in carrying out their administrative work during the Covid-19 pandemic. The concept used was This study used an exploratory case study. A qualitative case study method was used to obtain information about the constraints and consequences of the Covid-19 pandemic on secretaries, administrative assistants, and administration staff. A list of semi-structured questions was developed based on the related literature and was used to collect in-depth information. The findings of this study revealed some challenges and constraints experienced by the 15 informants.